2001
DOI: 10.1073/pnas.051013798
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of gene expression in human CD15+myeloid progenitor cells

Abstract: We performed a genome-wide analysis of gene expression in primary human CD15 ؉ myeloid progenitor cells. By using the serial analysis of gene expression (SAGE) technique, we obtained quantitative information for the expression of 37,519 unique SAGE-tag sequences. Of these unique tags, (i) 25% were detected at high and intermediate levels, whereas 75% were present as single copies, (ii) 53% of the tags matched known expressed sequences, 34% of which were matched to more than one known expressed sequence, and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
3
27
0
3
Order By: Relevance
“…Sequences from 32 novel tags matched known expressed sequences, and reactions for 49 novel tags did not generate qualified sequences. This result, as well as our earlier study on CD15 ϩ cells (11), indicates that the novel SAGE tags we have identified truly represent a large number of novel genes. The conversion of novel SAGE tags into 3Ј ESTs provides an efficient way to identify novel genes on a large scale.…”
Section: Conversion Of Novel Sage Tags Into Novel 3 Estssupporting
confidence: 83%
See 1 more Smart Citation
“…Sequences from 32 novel tags matched known expressed sequences, and reactions for 49 novel tags did not generate qualified sequences. This result, as well as our earlier study on CD15 ϩ cells (11), indicates that the novel SAGE tags we have identified truly represent a large number of novel genes. The conversion of novel SAGE tags into 3Ј ESTs provides an efficient way to identify novel genes on a large scale.…”
Section: Conversion Of Novel Sage Tags Into Novel 3 Estssupporting
confidence: 83%
“…SAGE Performance. SAGE was performed with our modified SAGE protocol (10), and the data were processed by use of our procedure (11).…”
Section: Methodsmentioning
confidence: 99%
“…The result revealed a similar distribution of genes between the two studies in various abundance classes, with minor variation largely due to sampling depth (Table III). In most of the SAGE studies, over 80% of unique tags were found present at low copy numbers (#5 tags), and around 50% of them were detected only once in a genome (Chrast et al, 2000;Lee et al, 2001;Fizames et al, 2004).…”
Section: Distribution Of Sage Tags In Rice Genomementioning
confidence: 99%
“…Poly(A 1 ) RNA isolation, cDNA synthesis, and SAGE library construction were performed according to a published protocol (Lee et al, 2001). Briefly, mRNAs were purified with the Oligotex mRNA Mini kit (Qiagen USA, Valencia, CA) and double-stranded cDNAs were synthesized from the fractioned poly(A 1 )-containing mRNAs with 5#-biotinylated 3#-anchored oligo(dT) primers (5#-biotin-ATCTAGAGCGGCCGCdT16[A/G/CA/CG/ CC]-3#).…”
Section: Plant Materials and Sage Library Constructionmentioning
confidence: 99%
“…TMSBX4 is an actin sequestering peptide that is highly expressed in CD15 þ myeloid progenitor cells, 33 and is involved in the differentiation of lymphocytes, macrophages, and granulocytes. 34 TMSBX4 has been shown to inhibit growth of AML cell lines, 35 suggesting that decreased expression in AMKL cells may promote proliferation compared to TL cells.…”
Section: Resultsmentioning
confidence: 99%